2008
DOI: 10.1007/s11746-007-1191-9
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Melting Points, Specific Heat Capacity and Enthalpy of Catfish Visceral Oil During the Purification Process

Abstract: Changes in melting points, enthalpy, and specific heat capacity of catfish visceral oil at each step of the purification process were studied. Melting points of -46.2 to 21.2°C for crude oil, -45.9 to 11.5°C for degummed oil, -44.3 to 11.4°C for neutralized oil, -47.1 to 9.9°C for bleached oil and -52.3 to 8.0°C for deodorized oil were observed. Enthalpy (kJ/kg) was 74.1 for crude oil, 74.7 for degummed oil, 75.1 for neutralized oil, 79.3 for bleached oil, and 84.3 for deodorized oil. The specific heat capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 18 publications
0
20
0
7
Order By: Relevance
“…The 2nd and the 3rd peaks appear around the temperature of −17.2 and −6.3 °C, respectively. This melting point at −6.3 °C may be attributed to the presence of linoleic acid (C18:2) and linolenic acid (C18:3), whose melting points range from −5.0 to −13.0 °C (Sathivel and others 2008b). The 4th peak melts close to 0 °C which also might be attributed to the moisture in the sample (Berjak and others 1992; Conner and Bonner 2001).…”
Section: Resultsmentioning
confidence: 99%
“…The 2nd and the 3rd peaks appear around the temperature of −17.2 and −6.3 °C, respectively. This melting point at −6.3 °C may be attributed to the presence of linoleic acid (C18:2) and linolenic acid (C18:3), whose melting points range from −5.0 to −13.0 °C (Sathivel and others 2008b). The 4th peak melts close to 0 °C which also might be attributed to the moisture in the sample (Berjak and others 1992; Conner and Bonner 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Fatty acids have their own melting points; therefore, sharp peaks were not observed for the oil. Sathivel et al (2008a) reported that the DSC thermograms of purified catfish oil showed sharper and narrower peaks than unpurified fish oil. The melting points of fish oil were sharper after each purification step that removed impurities from the oil.…”
Section: Thermal Analysis Of Upo Aeao No and Naeao Oilsmentioning
confidence: 99%
“…The amounts of impurities present in the red salmon oil influence the rheological and thermal properties of the oils [9,10]. Knowledge of the rheological properties at different temperatures can be used to solve problems related to the transfer or movement of bulk quantities of liquids, i.e., at low temperatures and flow rates, impurities in the oils can precipitate on the pipe walls causing pressure and other problems in the delivery system.…”
Section: Introductionmentioning
confidence: 99%